2020
DOI: 10.2166/wst.2020.325
|View full text |Cite
|
Sign up to set email alerts
|

Developing a microbial consortium for removing nutrients in dishwasher wastewater: towards a biofilter for its up-cycling

Abstract: Microbial consortia are effective biofilters to treat wastewaters, allowing for resource recovery and water remediation. To re-use and save water in the domestic cycle, we assembled a suspended biofilm, a ‘biofilter’ to treat dishwasher wastewater. Bacterial monocultures of both photo- and hetero-trophs were assembled in an increasingly complex fashion to test their nutrient stripping capacity. This ‘biofilter’ is the core of an integrated system devoted to re-using and upcycling of reconditioned wastewater, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…For the treatment of wastewater (Congestri et al, 2020) Frontiers in Bioengineering and Biotechnology frontiersin.org increase the growth of chilli plants (Swandi et al, 2019). Microbial consortium TCM was selected in a study for field trial and showed that TCM consortium improves the effectiveness of rhizospheric nutrition and promotes the growth of Camellia sinensis (Shang and Liu 2020).…”
Section: Pseudomonas Sp Acinetobacter With Trichormus Variabilismentioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of wastewater (Congestri et al, 2020) Frontiers in Bioengineering and Biotechnology frontiersin.org increase the growth of chilli plants (Swandi et al, 2019). Microbial consortium TCM was selected in a study for field trial and showed that TCM consortium improves the effectiveness of rhizospheric nutrition and promotes the growth of Camellia sinensis (Shang and Liu 2020).…”
Section: Pseudomonas Sp Acinetobacter With Trichormus Variabilismentioning
confidence: 99%
“…Two studies show the engineering of rhizobacterial consortium for the treatment of contaminated soil and wastewater ( Yankey et al, 2021 ) ( Congestri et al, 2020 ) a study is conducted for the metagenomic analysis of PGPR consortium members to uncover the varieties of diesel degrading rhizobacterial consortium and their genetic variation ( Eze et al, 2021 ). The degradation of pyrene by the synergistically rhizobacterial consortium has been studied ( Cavalu and Damian, 2003 ; Wanapaisan et al, 2018 ).…”
Section: Application Of Natural Rhizobacterial Consortium and Enginee...mentioning
confidence: 99%
“…If heat can be recovered from greywater streams (Section 3.2.1), can the wastewater itself not be treated, upcycled, and recirculated for use in subsequent cycles? For this purpose, Congestri and colleagues [64] developed and tested a bio-filter harbouring a synergistic consortium-photosynthetic cyanobacteria releasing oxygen for uptake by aerobic heterotrophs in the filter, which in turn provide carbon dioxide to the former. While the uncontrolled biofilms with pathogenic mycobacterial colonies (Section 3.4.1) are undesirable, 'engineered' ones cultivated for bio-remediation of wastewater-in this case, resulting in an appreciable reduction in the nitrogen and phosphorus load-are extremely useful agents in a circular bio-economy [85].…”
Section: Water and Wastewatermentioning
confidence: 99%
“…Biofilm development in artificial environments and mechanical devices, particularly those with high water loads, can yield to the risk of contamination by pathogens, for example in dishwashers 9 , 10 . Paradoxically, though, selected microbial populations can also be used to treat the effluents of those machines, such as the biofilter recently developed to treat dishwasher wastewater 11 . Biofilms are also found in industrial and domestic washing machines, where, interestingly, the majority of the microbial strains isolated formed substantial biofilms in washing machines worldwide 12 .…”
Section: Introductionmentioning
confidence: 99%